Kreatif Tanpa Gadget: Pelatihan Kerajinan Tangan dari Barang Bekas - Dewi, Ika Parma; Hutagalung, Juli Elprida; Naufal, Kms Muhammad; Muslimah, Farhatun; Yeni, Nia Febrima; Melinda, Sari; Hasali, Ivan; Anwar, Artesia; Analismi, Wenti Julia (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Industry 4.0 marks a significant transformation in production processes through the use of digital technologies such as the Internet of Things (IoT) and big data analysis, which enables high efficiency and communication between devices. However, this progress also affects Generation Z, who is very connected to digital technology, presenting challenges in the form of dependence on gadgets. To overcome this problem, it is important to create activities that divert attention from technology, while encouraging creativity. One of the proposed solutions is training in handicrafts from used goods. Through a program carried out at the Darul Ma'arif Al-Karimiyah Orphanage, Padang, this training aims to increase children's creativity by recycling inorganic waste into valuable products. The 3R (Reduce, Reuse, Recycle) approach is used to teach environmentally sound waste management. As a result, children are expected to be able to produce useful work and improve the quality of life without relying on digital technology. The methods used are observation, outreach and practical training, with material covering the dangers of gadget addiction and waste recycling techniques. The results of the training showed an increase in children's creativity, who were able to produce products such as tissue holders, wall hangings and photo frames. The results of the feedback given to orphanage children showed that 90% of respondents stated that they strongly agreed with the training activities that had been carried out.